Does financial transparency substitute corporate governance to improve stock liquidity? Evidence from emerging market of Pakistan - Ali, Shuaib; Zhongxin, Wu; Ali, Zahid; Usman, Muhammad; Zhuoping, Yu (Frontiers in Psychology, 2022)
The aim of this study is to empirically analyze the impact of corporate governance on stock liquidity and the moderating role of financial transparency, through the lens of information asymmetry and agency theory. The sample consists of non-financial firms listed on the Pakistan stock exchange during the 2009–2019 period. The study used an instrumental variable approach and new corporate governance index, developed with principal component analysis, to demonstrate a relationship between corporate governance and stock liquidity. The results show a significant, positive relationship between the corporate governance index and stock liquidity, suggesting that well governed firms have high liquidity. To the best of our knowledge, this is the first finance study to investigate the moderating impact of financial transparency on the relation between corporate governance and stock liquidity. The results show that financial transparency, as measured by multiple proxies, has a negative moderating impact on the relationship between corporate governance and stock liquidity, suggesting that corporate governance in Pakistan is weak. Together, the results suggest that Pakistani firms use financial transparency as a substitute for corporate governance to improve stock liquidity. The results are robust to a series of endogeneity checks using alternative proxies of stock liquidity.